2008
DOI: 10.1186/1465-9921-9-74
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related air pollution and respiratory symptoms among asthmatic children, resident in Mexico City: the EVA cohort study

Abstract: Respiratory symptoms in asthmatic children were significantly associated with exposure to traffic exhaust, especially from natural gas and diesel-fueled vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 34 publications
(31 reference statements)
3
53
1
1
Order By: Relevance
“…All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012). Most of the studies observed positive associations between short-term exposure to NO 2 (or nitrogen oxides) for different lags and respiratory symptoms, such as coughing and wheezing (O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Andersen et al, 2008b), as well as for exhaled nitric oxide (Sarnat et al, 2012) and also for pulmonary function decrease (O'Connor et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al 2009;Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008) in children, although not all of them were statistically significant (Dales et al, 2009). One article reported numerical data only for PM (Min et al, 2008).…”
Section: Panel Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012). Most of the studies observed positive associations between short-term exposure to NO 2 (or nitrogen oxides) for different lags and respiratory symptoms, such as coughing and wheezing (O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Andersen et al, 2008b), as well as for exhaled nitric oxide (Sarnat et al, 2012) and also for pulmonary function decrease (O'Connor et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al 2009;Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008) in children, although not all of them were statistically significant (Dales et al, 2009). One article reported numerical data only for PM (Min et al, 2008).…”
Section: Panel Studiesmentioning
confidence: 99%
“…A PubMed search identified 11 new articles: 6 from the Americas (Sarnat et al, 2012;O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al, 2009), 2 from Europe (Andersen et al, 2008b;Coneus & Spiess, 2012), and 3 from Asia (Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008). All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012).…”
Section: Panel Studiesmentioning
confidence: 99%
“…Escamilla-Nuñez et al 2008;Romieu et al 2008). Recent epidemiological studies report neuro-inflammation in otherwise healthy children residing in MCMA (Calderón-Garcidueñas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos usaram métodos combinados para avaliar a exposição ao tráfego 55,56 . Outros métodos de avaliação da exposição aos poluentes veiculares, como por exemplo, o uso de questionários, em que são reportados os níveis de tráfego, monitores instalados em residências, amostradores pessoais ou passivos e dados de estação de monitoramentos também são aplicáveis [57][58][59][60][61] .…”
Section: Avaliação Da Exposição à Poluição Relacionada Ao Tráfegounclassified